البنية السردية في رواية عرس الزين للطيب صالح - شوارفية, خيرة (كلية الأدب العربي والفنون, 2024)
تدور الدراسة في هذا البحث حول البنية السردية في رواية "عرس الزين" للروائي السوداني الطيب صالح. تعد البنية السردية في الرواية من أهم ما أولاه النقاد والدارسون والكتاب عناية خاصة ودقيقة، باعتبارها أنّها تدرس الرواية من حيث بناءها وتشكيلها السردي، من الزمان والمكان ومن حيث الشخصياتوالأحداث، وقد عمل البحث هذا إلى تطبيق وقراءة واستدراج البنية السردية على مدونة سردية سودانية حديثة ومعاصرة وهي رواية "عرسالزين"، حيث قامت الخطة على مقدمة، ومدخل وفصلين، فتم تخصيص المدخل لقراءة وتعريف بعنوان البحث من مفهوم البنية والسرد والرواية، أمّا الفصل الأول فكان نظريا وتم فيه التعريف ببعض المصطلحات والمفاهيم المتعلقة بالبنية السردية في الرواية. كما ذكر فيه عناصر البنية السردية من (بنية الزمن، بنية المكان، بنية الشخصيات، بنية الأحداث). أمّا الفصل الثاني كان تطبيقيا بعنوان تجليات البنية السردية في رواية "عرس الزين"، وتم فيه دراسة بنيات الزمان والمكان ثمّ الشخصيات والأحداث، واختتم هذا البحث في نهاية بخاتمة احتوت أهم النتائج المتواصل إليها من هذه الدراسة. The study in this research revolves around the narrative structure in the novel “The Wedding of Zein” by the Sudanese novelist TayebSalih. The narrative structure in the novel is one of the most important things that critics, scholars, and writers have paid special and careful attention to, as it studies the novel in terms of its structure and narrative formation, in terms of time and place, and in terms of characters and events. This research aimed to apply, read, and introduce the narrative structure to a modern and contemporary Sudanese narrative blog. It is the novel “The Wedding of Zein”, where the plan was based on an introduction, an introduction and two chapters. The introduction was allocated to reading and defining the title of the research from the concept of structure, narration and the novel. As for the first chapter, it was theoretical and some terms and concepts related to the narrative structure in the novel were introduced. He also mentioned the elements of narrative structure, including (the structure of time, the structure of place, the structure of characters, and the structure of events). The second chapter was applied, entitled “Manifestations of the Narrative Structure in the Novel “The Wedding of Zein,” in which the structures of time and place, then the characters and events, were studied. This research concluded at the end with a conclusion that contained the most important results reached from this study.
Keywords: البنية.السرد .الرواية. -عرس الزين. الزمكانية. الشخصيات.الحدث.; Structure. -Narrative -Narrative. - Al-Zein wedding. -Space-time. -Characters. - the event.